Study on Nitrogen Content of Cellulose Carbamates by Fourier Transform Infrared Spectroscopy - Guang-Mei, Chen (Asian Journal of Chemistry, 2010)
Cellulose carbamates were synthesized by using microcystalline cellulose and cellulose pulp as raw materials. The Fourier transform infrared (FTIR) spectra were recorded and used to determine the nitrogen content of cellulose carbamate. The accurate results of the nitrogen content can be obtained with the deconvolution method replacing the baseline method when the nitrogen content is not more than 4%.